Natural rate of output, supply side potential and the long term sustainable growth band for Singapore. - Lee, Dennis Wee Keong. (2010)
Being a small and open economy heavily dependent on the external economy for her economic growth, Singapore is in a highly precarious position to external shocks and performances of her trading partners. The discussion on Singapore's medium-term sustainable growth path for the year 2000 and beyond becomes more intense as her economy matures since the ability to formulate macro policy consistent with the potential growth would ensure price stability and optimal resource allocation. The official estimates on the Republic's medium-term growth by the various ministries range from 4% to 8.5%, and the diverging forecasts point to the differing views on the underlying structural changes and exogenous factors which are regarded to be paramount. This paper attempts to pin down the potential output growth of Singapore by using a consistent econometric estimation approach, which integrates the potential output with the natural rate of unemployment. Based on the three-stage least square estimation technique incorporating rational expectations approach, our results suggest that Singapore's economic growth has been hovering at her potential level between 1988 and 1996 with the potential output found to be ranging between 8.5% to 11%. The natural rate of unemployment declines steadily from 6% in 1988 to about 3.5% in 1996, slightly above the actual unemployment rate which stabilized at 2% since the 1990's as the Republic's dependence on foreign labor force participation increases.